Knowledge, attitudes, and experiences in suicide assessment and management: a qualitative study among primary health care workers in southwestern Uganda - Rukundo, Godfrey Z.; Wakida, Edith K.; Maling, Samuel; Kaggwa, Mark M.; Sserumaga, Baker M.; Atim, Letizia M.; Atuhaire, Clara D.; Obua, Celestino (BMC psychiatry, 2022)
Background: Suicide is one of the leading causes of death globally, with over 75% of all suicides occurring in low and middle-income Countries. Although 25% of people have contact with their health care workers before suicide attempts, most never receive proper suicide assessment and management. We explored primary care health workers’ knowledge, attitudes, and experiences in evaluating and managing suicidality in structured primary healthcare services in Uganda. Methods: This was a cross-sectional qualitative study among health workers in southwestern Uganda from purposively selected health facilities. A semi-structured interview guide was used, and data were analyzed using thematic analysis. Results: The in-depth interviews were conducted with 18 individuals (i.e., five medical doctors, two clinical officers, two midwives, and nine nurses) from 12 health facilities in the five selected districts. Four themes emerged from the discussions: a) Knowledge and attitudes of primary healthcare workers in the assessment and management of suicidality, b) Experiences in the assessment and management of suicidality, c) challenges faced by primary healthcare workers while assessing and managing suicidality, and d) Recommendations for improving assessment and management of suicidality in PHC.Most participants were knowledgeable about suicide and the associated risk factors but reported challenges in assessing and managing individuals with suicide risk. The participants freely shared individual experiences and attitudes in the assessment and management of suicide. They also proposed possible ways to improve the evaluation and management of suicidality in PHC, such as setting up a system of managing suicidality, regularizing community sensitization, and training health workers. Conclusion: Suicidality is commonly encountered by primary health care workers in Uganda who struggle with its assessment and management. Improving the knowledge and attitudes of primary health care workers would be a big step towards ensuring equitable services.
Keywords: Suicide assessment; Management of suicidal behaviors; Primary health care; Uganda